2018
DOI: 10.29219/fnr.v62.1524
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional, biochemical and sensory properties of instant beverage powder made from two different varieties of pearl millet

Abstract: IntroductionThe traditional method of producing instant foods involves producing a gelatinised paste from the preferred grain flour and proceeding to dry it using a drum drier. This produced a flaked product, which can be used as is or ground and sieved to obtain the desired particle size. With the advent of extrusion cooking technology and diverse production processes associated with the technology, food products including instant foods from cereals were developed.ObjectivesThe primary objective of this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 29 publications
1
11
2
Order By: Relevance
“…The results of energy content showed that the samples were significantly different (p<0.05). The energy value of the instant mango drink powder was similar than reported by Mohammed et al (2017) for instant sorrel (Zobo) drink and lower than observed by Farzana et al (2017) for vegetable soup powder and Obilana et al (2018) for instant beverage powder.…”
Section: Proximate Analysis Of Instant Mango Drink Powdersupporting
confidence: 65%
See 4 more Smart Citations
“…The results of energy content showed that the samples were significantly different (p<0.05). The energy value of the instant mango drink powder was similar than reported by Mohammed et al (2017) for instant sorrel (Zobo) drink and lower than observed by Farzana et al (2017) for vegetable soup powder and Obilana et al (2018) for instant beverage powder.…”
Section: Proximate Analysis Of Instant Mango Drink Powdersupporting
confidence: 65%
“…In contrast, the lower value (0.7±0.03%) was found in Sample D. The results of protein content showed that the samples were significantly different (p<0.05). The protein content of the instant mango drink powder was higher than reported by Akhter et al (2010) for instant mango juice powder and lower than reported by Farzana et al (2017) for vegetable soup powder, Mohammed et al (2017) for instant sorrel (Zobo) drink and Obilana et al (2018) for instant beverage powder.…”
Section: Proximate Analysis Of Instant Mango Drink Powdercontrasting
confidence: 55%
See 3 more Smart Citations